Speech Acts in the Closing Speech of the G20 Summit by President Joko Widodo “We Must End The War” - Hadiati, Chusni; Muttaqin, Usep; Yulianita, Nadia Gitya (Bina Nusantara University, 2024)
The research aimed to discover the types of speech acts that existed and elaborated them according to the national and international context. The G20 group consisted of 19 countries and Spain as a permanent guest with the largest economies in the world plus one intergovernmental and supranational organization, namely, the European Union. The research categorized the president’s utterances into five types of speech acts: representatives, expressives, declarations, directives, and commissives. Among the 49 utterances, representatives were the most prevalent, indicating the president’s intent to present factual statements in front of global leaders. The research highlighted the strategic use of plural subjects in directives to involve both the speaker and the audience in the commitment. Expressives were employed to convey gratitude and welcome world leaders, showcasing the president’s politeness and respect. Commissives reflected the president’s commitment to global issues such as peace, food sustainability, and economic recovery. The researchers collected the data through several steps. The first was transcribing the speech; afterward, the researchers picked and classified those utterances based on Searle’s classification of speech acts. The findings underscore the importance of context in understanding the meaning and intention behind political speeches at international forums like the G20 Summit.